Effect of HIPEC according to HRD/BRCAwt genomic profile in stage III ovarian cancer: Results from the phase III OVHIPEC trial. Issue 8 (4th June 2022) - Koole, Simone N.; Schouten, Philip C.; Hauke, Jan; Kluin, Roel J. C.; Nederlof, Petra; Richters, Lisa K.; Krebsbach, Gabriele; Sikorska, Karolina; Alkemade, Maartje; Opdam, Mark; Schagen van Leeuwen, Jules H.; Schreuder, Henk W. R.; et al.
Abstract: The addition of hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin to interval cytoreductive surgery improves recurrence‐free (RFS) and overall survival (OS) in patients with stage III ovarian cancer. Homologous recombination deficient (HRD) ovarian tumors are usually more platinum sensitive. Since hyperthermia impairs BRCA1/2 protein function, we hypothesized that HRD tumors respond best to treatment with HIPEC. We analyzed the effect of HIPEC in patients in the OVHIPEC trial, stratified by HRD status and BRCA m status. Clinical data and tissue samples were collected from patients included in the randomized, phase III OVHIPEC‐1 trial. DNA copy number variation (CNV) profiles, HRD‐related pathogenic mutations and BRCA1 promotor hypermethylation were determined. CNV‐profiles were categorized as HRD or non‐HRD, based on a previously validated algorithm‐based BRCA1 ‐like classifier. Hazard ratios (HR) and corresponding 99% confidence intervals (CI) for the effect of RFS and OS of HIPEC in the BRCA m, the HRD/ BRCA wt and the non‐HRD group were estimated using Cox proportional hazard models. Tumor DNA was available from 200/245 (82%) patients. Seventeen (9%) tumors carried a pathogenic mutation in BRCA1 and 14 (7%) in BRCA2. Ninety‐one (46%) tumors classified as BRCA1 ‐like. The effect of HIPEC on RFS and OS was absent in BRCA m tumors (HR 1.25; 99%CI 0.48‐3.29), and most present in HRD/ BRCA wt (HR 0.44; 99%CI 0.21‐0.91), and non‐HRD/ BRCA wt tumors (HR 0.82; 99%CI 0.48‐1.42), interaction P value: 0.024. Patients with HRD tumors without pathogenic BRCA1/2 mutation appear to benefit most from treatment with HIPEC, while benefit in patients with BRCA1/2 pathogenic mutations and patients without HRD seems less evident. What's new?: Serous ovarian cancers that are homologous recombination deficient (HRD) often are sensitive to platinum‐containing chemotherapy. Whether hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin benefits patients with HRD tumors, however, remains unclear. In this study, an algorithm‐based HRD classifier was validated using data and tissue derived from the randomized, phase III OVHIPEC‐1 trial. Interval cytoreductive surgery and HIPEC was found to prolong recurrence‐free and overall survival moin patients with HRD/ BRCA1 wild‐type ovarian cancers. Responses of BRCA1/2 ‐mutated and HR‐proficient ovarian cancers to HIPEC were less pronounced. The HRD classifier is a promising tool for identifying ovarian cancer patients who may benefit from HRD relying treatment modalities.